Investigating a role of HER3 in anti-HER2 target therapy in breast cancer - Hashimoto, K (2014)
Background HER2-positive breast cancer is a poor prognostic subgroup, even if treated with anti-HER2 directed therapy. Trastuzumab is an important HER2-targeting antibody but only limited patients respond to this drug, and acquired resistance is a common problem. HER3 has been shown to be a key candidate in mediating resistance to trastuzumab and other ErbB inhibitors. The aims of the project are to investigate the resistance mechanisms and the relevant biomarkers in relation to trastuzumab treatment and resistance in HER2-positive breast cancer, in particular, HER3 subcellular localisation and HER3 phosphorylation. Methods Effects of trastuzumab on HER3 subcellular localisation and HER3 phosphorylation in relation to MET receptor were studied using western blots, nuclear fractionation, confocal microscopy, and immunoprecipitation in a panel of HER2-positive cell lines, including SKBr3 and BT474 breast cancer cells in which trastuzumab resistance was induced by long-term drug exposure. Effects of drug and knockdown experiments were tested by cell viability and proliferation assays. HER3 and MET expression was assessed by immunohistochemistry in xenograft tumours and human tissue samples, and clinical impact was assessed in different cohorts of HER2-positive breast cancer patients. Results Acquired trastuzumab resistant SKBr3 cells showed an increase of nuclear HER3100kD, which was derived from C-terminus of HER3. Nuclear HER3100kD could be due to the proteolytic cleavage of HER3 since it was reduced by ADAM17 or gamma-secretase inhibitor. In a panel of HER2-positive cell lines and xenograft samples, nuclear HER3 was observed only in the resistant cells. In addition, nuclear HER3 was associated with poor progression-free and overall survivals in HER2-positive breast cancer patients. It was also found that HER3 phosphorylation was maintained in acquired trastuzumab resistant cells, which was contributed by the ligand independent interaction of MET and HER3. Higher MET expression was associated with better overall survival in HER2-positive, breast cancer patients who were not treated with trastuzumab. Conclusions Nuclear HER3 was found in trastuzumab resistant cells and appeared to result from HER3 proteolytic cleavage mediated by ADAM17 and gamma-secretase. Further studies are required to investigate its mechanism and to identify the HER3 cleavage sites. MET was a key factor in maintaining HER3 phosphorylation during trastuzumab resistance. Lastly, nuclear HER3 and MET could be two potential biomarkers in HER2-positive breast cancer.